A dc magnetization and local permeability study of the HgBa2CuO4+delta superconductor - Stamopoulos, D.; Pissas, M. (SUPERCONDUCTOR SCIENCE & TECHNOLOGY, 2001)
Local Hall probe ac permeability and global dc SQUID magnetization measurements were used to construct the phase diagram of the vortex matter for two HgBa2CuO4+delta single crystals with different amounts of disorder. Emphasis was given near T-c and for low magnetic fields H-dc < 1 kOe. For the nearly optimally doped crystal with T-c = 94.8 K, the second peak line H-sp and the respective onset line H-min of the magnetization loops end at (T*, H*) = (88 K, 2 kOe) on the irreversibility line, while for the crystal of lower T-c (= 89.9 K) decreases monotonically and terminates just below T-c In addition, for the crystal with T-c = 89.9 K the local permeability measurements (as a function of temperature or dc magnetic field) revealed a peak in the screening current just below the onset of the diamagnetic screening. The possible sublimation character of the melting transition, the two-stage melting scenario and a Bragg to vortex glass transition are discussed. The different behaviours observed between the two crystals is attributed to the different amount of disorder.